Gravminner som oppfordring til forbønn - Stige, Morten (Hikuin, 2017)
Funerary effigys as invitations for prayers of indulgence By Morten Stige In the early middleages most Christian funerary monuments were depicting crosses or vegetative scrolls to symbolise the Christian identity of the deceased. Corresponding with the growing importance of the concept of purgatory during the thirteenth century the effigy and the full figure grave slab became widespread in the funerary art. There came a new need to be remembered as an individual to become the object of prayers of indulgence. During the coming centuries there was a development of funerary monuments which became increasingly rhetorically effective in getting attention and entice the beholder to act. The performative approach is rewarding as it seems to correspond to the intentions of the patrons behind the grave monuments. Through the depictions of the deceased in the act of prayer and added texts which either ask directly for the prayer of the beholder, reminds him of a prayer as a good act or even in some cases gives a number of days in indulgence to whom prays for the diseased, the grave monument strongly encourages the act of praying. Another group of grave slabs can be understood as performative in them selves as they depict the deceased in the act of praying to one or more of his patron saints, with a textband praying that the saint as a mediator in turn will pray for his soul. Thus an eternal prayer is constructed, similar to the Buddhist prayer wheel.